Inquiry Based Learning Model Natural Phenomena to Improve The Curiousity and Mastery of Teh Concept of Junior High School Student - Hadiryanto, Soleh; Thaib, Dina (Universitas Pendidikan Indonesia, 2015)
The purpose of this study was to analyze the increase curiousity and mastery of the concept of junior high school students after participating in inquiry learning based on the natural phenomenon of motion plant material. The method used is experiment using a randomized design Pretest-Posttest Control Group Design. In the conduct of research, classroom-based inquiry learning experiments using natural phenomena and grade control using conventional learning. The instrument used is the concept mastery tests and questionnaires curiousity students. The results of calculation of N-gain scores showed a rise curiousity and mastery of concepts students both in the experimental and control groups, but the increase in the experimental group was higher than the control group. Through two different test average showed a significant difference curiousity improvement and mastery of concepts students at level Î± of 0.05 between students who learn by inquiry-based learning and the study of natural phenomena with conventional learning. Increased curiousity and mastery of concepts students learn the natural phenomena based inquiry learning in the experimental group is higher than that of learning through conventional teaching in the control group.